Raw grain as human food - Hastings, Milo M. (My University, 1906)
Introduction: The determination of the best diet for man has been attempted by analogous reasoning from the diets of lower animals, but for reasons clear to a biologist such conclusions avail nothing. Likewise the attempt to determine the proper diet from a study of prevailing diets will, for obvious reasons, not correct prevailing faults. With this latter source of information has been combined the results of the physiological chemist. Of this class of knowledge there is not much fault to find save its incompleteness. The development of this science must add greatly to the understanding of nutrition and the determination of the best diets but the chemist must admit that the subtler organic changes that constitute the vital processes and determine the intensity and length of life are at present beyond his reach. If all these methods fall short of solving the problem of the optimum diet of man, by what method, it may be asked, is the problem to be solved. There is, it seems to me, one final test to which any theory of diet must submit and that is the test of careful experimental study of the effect of the diet upon men. The opinion of the mass of men in regard to food is not to be accepted as it is based upon immediate pleasures; neither the rapidity nor completeness of digestion nor the results of an isolated experiment are to be accepted as conclusive, for these may be only incidental. The worth of a diet for man is to be determined by the effect of that diet upon his fitness for living and, as with the dairy cow, this must first be determined for the race by combined experiment and then adapted in the details to each individual.
Citation: Hastings, Milo M. Raw grain as human food. Senior thesis, Kansas State Agricultural College, 1906.
Morse Department of Special Collections
Keywords: Food; Grains; Human Diet; Physiology; Theses